The Effect of Constructive Play on Early Childhood Mathematics Skills in Indonesia: A Meta-Analysis - Abineno, Fransina O; Yeuw, Fince F.; Yustinus Wangguway (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Many studies have explored the impact of constructive play on early childhood early math skills and have shown mixed results. Therefore, the purpose of this meta-analysis is to re-examine the effect of constructive play on early childhood early math skills. This research is a meta-analysis with a quantitative approach. This study involved the results of research from several researchers obtained through google scholar searches from 2014 to 2024 using the PRISMA stages of identification, screening, eligibility, and inclusion. Data analysis in this meta-analysis research uses the help of the OpenMEE application with stages including publication bias test, heterogeneity test, calculating the effect size of each primary study, and making conclusions from the analysis results. The results of the effect size analysis of 22 studies published in a decade showed that constructive play positively contributed to the overall effect size of the studies in the Very Large category with a value of 3.145. In addition, this study explored the types of constructive play and early math skills of the targeted young children. The most effective type of constructive play was the magnetic board with a value of 7.263. Meanwhile, the targeted early math skill was mathematical logical thinking with a score of 8.138. The findings of this research indicate that constructive games provide a more effective influence and should be applied in improving early childhood early math skills.